Evaluation of rheological, mechanical and microstructure performance of hot mix asphalt (HMA) incorporating with agricultural waste: a review - Kamaruzaman, Nur Atikah; Wan Azahar, Wan Nur Aifa; Kasim, Norhidayu; Nor Hairin, Assayidatul Laila; Ismail, Norfarah Nadia (UKM Press, 2025)
The increasing demand for sustainable and eco-friendly materials in the construction industry has led to the exploration of agricultural waste as an alternative modifier in hot mix asphalt (HMA). Agricultural waste is one of the potential materials that can be used as bitumen modifier due to the abundance of waste been dumped without being utilized properly. This review aims to evaluate the effects of incorporating various types of agricultural waste on the rheological, mechanical, and microstructural performance of HMA. Specifically, it focuses on the influence of materials such as rice husk ash, sugarcane bagasse, Palm Oil Fuel Ash (POFA), coconut and other agricultural by products on the physical properties of asphalt binder and mix. Additionally, the review highlights changes in the microstructure of the asphalt mixture, observed through scanning electron microscopy (SEM) and other characterization techniques. The findings suggest that agricultural waste materials have the potential to enhance the performance of HMA by improving its mechanical properties, increasing rutting resistance, and promoting sustainability in road construction. However, challenges such as optimal dosage, compatibility with conventional asphalt components, and long-term performance stability are also identified. Therefore, chemical and physical treatment need to be done to promote the compatibility between agricultural waste and bitumen. This paper provides a comprehensive overview of current research, offering valuable insights for future studies and practical applications in the integration of agricultural waste in asphalt pavements.